COMPARISON OF HEALTH EDUCATIONAL THROUGH LECTURER AND AUDIO VISUAL METHOD ABOUT PHYSICAL ACTIVITY IN PREGNANT WOMAN DURING 3RD SEMESTER PREGNANCY BENGKULU IN CITY - Sastianto Ahmad; Flora Rostika; Hartati Hartati (Sriwijaya University Learning and Education International Conference, 2018)
Physical activity during pregnancy can improve the physical fitness and muscle conditioning needed to Facilitate labor. Health education and audiovisual using conventional methods is expected pregnant women know the importance of physical activity during pregnancy. The purpose of this research is to know the difference of health education and audiovisual conventional method using about physical activity during pregnancy in pregnant mother of 3rd semester in Bengkulu City. Cross-sectional design using a quasi-experimental method, using two gruop pretest posttest design. The sample was 48 pregnant women. The sampling technique in this research is done in a sequential way. The research instrument used questionnaire. Data analysis using paired sample test and independent sample test. The result of paired sample test of both groups of media at the level of knowledge Obtained p value of